Bimbingan Teknis Pelaporan Keuangan Yayasan Isak 35 Pada Yayasan Pendidikan Kutai Timur - Muhammad Harits Zidni Khatib Ramadhani; Muhammad Rinaldi; Yunita Fitria; Muhammad Abadan Syakura (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The implementation of community service activities aims to enhance understanding and skills in financial reporting for the iSAK 35 Foundation by the East Kutai Education Foundation. The technical guidance method is employed as the primary approach in this intervention, through a series of tailored training sessions, workshops, and consultation sessions to meet the Foundation's needs. An analysis of the effectiveness of this intervention is conducted by evaluating the participants' knowledge and skills enhancement, as well as changes in the Foundation's financial reporting practices. The results demonstrate a significant improvement in the comprehension of concepts and implementation of ISAK 35 financial reporting, alongside the adoption of best practices in Foundation financial management. The implications of this research encompass strengthening the Foundation's capacity in more effective and transparent financial management, as well as the potential to enhance the quality of financial reports to support accountability and transparency in managing the Foundation's funds and resources.